2017
DOI: 10.1007/s40069-016-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

FRP Confinement of Heat-Damaged Circular RC Columns

Abstract: To investigate the effectiveness of using fiber reinforced polymer (FRP) sheets in confining heat-damaged columns, 15 circular RC column specimens were tested under axial compression. The effects of heating duration, stiffness and thickness of the FRP wrapping sheets were examined. Two specimen groups, six each, were subjected to elevated temperatures of 500°C for 2 and 3 h, respectively. Eight of the heat-damaged specimens were wrapped with unidirectional carbon and glass FRP sheets. Test results confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Natural-flax fabric reinforced epoxy polymer material increases in peak load and fracture energy by 6-layer and it is 374 % and 4660 % and also S.E.M analysis show perfect bonding between materials [23]. Elevated temperatures should result the stress parameters in between FRP and concrete [24]. Round edged concrete members will help to decreases the stresses at the corners [25].…”
Section: Frp Strengthened Concrete Columnsmentioning
confidence: 96%
“…Natural-flax fabric reinforced epoxy polymer material increases in peak load and fracture energy by 6-layer and it is 374 % and 4660 % and also S.E.M analysis show perfect bonding between materials [23]. Elevated temperatures should result the stress parameters in between FRP and concrete [24]. Round edged concrete members will help to decreases the stresses at the corners [25].…”
Section: Frp Strengthened Concrete Columnsmentioning
confidence: 96%
“…Then they developed a design-oriented model to predict the compressive strength of unheated and heated concrete columns. Al-Nimry and Ghanem (2017) tested 15 FRP-confined specimens to investigate the effectiveness of FRP jackets in strengthening the heated concrete columns. They subjected their specimens to the temperature of 500°C for two and 3 h and then wrapped them by GFRP and CFRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…The columns strengthened using CFRP confinement had large stress concentration at the corners and failed by local debonding. Al-Nirmy and Ghanem [10] researched the behaviour of pre-damaged RC columns due to high temperatures and shown that the damaged columns when retrofitted using CFRP were able to increase the axial load but with the reduced ductility. Fukuyama et al [11] investigated the behaviour of RC columns under cyclic shear loading and concluded that CFRP strengthening was able to improve the performance of the damaged column than the control specimens.…”
Section: Introductionmentioning
confidence: 99%